Modulation of Micro RNA Expression and Osteoblast Differentiation by Nanotopography - Sartori, Elisa Mattias [UNESP]; Magro-Filho, Osvaldo [UNESP]; Silveira Mendonca, Daniela B.; Li, Xiang; Fu, Jianping; Mendonca, Gustavo (Quintessence Publishing Co Inc, 2018)
Purpose: This study evaluated the expression pattern of micro RNAs (miRNAs) on a surface with nanotopography compared with a smooth surface (control). Materials and Methods: Human mesenchymal stem cells (hMSCs) were plated on different surfaces and compared at 3, 7, and 14 days for alkaline phosphatase (ALP) activity, expression of genes (osterix [OSX], runt-related transcription factor 2 [RUNX2], bone morphogenetic protein 2 [BMP2], and ALP), and expression of miRNAs. Western blot was also used to detect osteogenic proteins (BMP2, OSX, and osteocalcin [OCN]). Scanning electron microscopy of cells plated onto the surfaces was obtained. Results: ALP activity on different surfaces was significantly greater in the nanotopography surface. At day 14, there was a 3.5-fold and a 9-fold increase for the RUNX2 and OSX genes, respectively. BMP2 and ALP also increased by fourfold and sevenfold compared with the control. Protein levels for OSX and BMP2 were also upregulated compared with the control group. Using RNA sequencing technology (RNA-Seq), a total of 117 miRNAs were found to be differentially expressed comparing the control (day 7) with the nanosurface (day 14). Forty-five miRNAs were upregulated, and 72 were downregulated. Several of the miRNAs that were differently expressed regulate osteogenic genes. For example, hsa-miR-135b-5p targets OCN, BSP, RUNX2, COL15A1, and OSX; hsa-miR-122-5p targets OPN; hsa-miR-196a-5p targets BMP4; hsa-miR-26b-5p targets BMP2; and hsa-miR-148b-3p targets OPN. Conclusion: Surfaces with nanotopography have the potential to improve the osseointegration response in order to reduce the osseointegration time and also increase bone formation around the implants, improving areas with low bone quality. Within the limitation of this study, nanotopography surfaces affected MSC differentiation to osteoblasts. Several miRNAs were differentially regulated by surface topography. These miRNAs could be related to the differentiation response to help control the osseointegration process.
Keywords: dental implants; human mesenchymal stem cells; micro RNAs; nanotopography; osteoblasts; surface properties